2017
DOI: 10.32890/jict2017.16.1.8216
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Cloud Computing Adoption in Small Medium Enterprises

Abstract: Cloud computing offers information technology (IT) infrastructure, platform, and various applications via the Internet with minimum start-up cost, network access to a shared pool of configurable computing resources, and pay-per-use services. Although the potential for cloud computing is evident and much of the extant research has been carried out on cloud computing adoption, empirical studies on the factors that influence cloud computing adoption in the Malaysian Small and Medium Enterprises (SMEs) are, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…However, to explain technology adoption, many scholars have used an approach that integrates more than one theory to explain technology adoption (Isma'ili et al, 2016a; Asiaei and Rahim, 2017; Ayoobkhan and Asirvatham, 2019) in order to better understand the factors that influence organizations when it comes to making a decision with regard to the adoption of technology. Among these theories, TEO and DOI have been employed widely in the information technology adoption domain and have provided empirical support as they focus on the organizational point of view (Asiaei and Rahim, 2017; Hassan et al, 2017; Abed, 2020; Skafi et al, 2020). In addition, both theories overlap in terms of the characteristics that strengthen the explanation of adoption.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to explain technology adoption, many scholars have used an approach that integrates more than one theory to explain technology adoption (Isma'ili et al, 2016a; Asiaei and Rahim, 2017; Ayoobkhan and Asirvatham, 2019) in order to better understand the factors that influence organizations when it comes to making a decision with regard to the adoption of technology. Among these theories, TEO and DOI have been employed widely in the information technology adoption domain and have provided empirical support as they focus on the organizational point of view (Asiaei and Rahim, 2017; Hassan et al, 2017; Abed, 2020; Skafi et al, 2020). In addition, both theories overlap in terms of the characteristics that strengthen the explanation of adoption.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, SMEs, especially in developed countries including Jordan, have acknowledged the importance of utilizing cloud computing as an innovation that permits the efficient use of technology, offers a decisive competitive advantage, and introduces cost-effective solutions (Al-Hujran et al, 2018). However, the level of its adoption still lags behind that of most other countries (Hassan et al, 2017). In the developing countries and in Jordan specifically, SMEs are still reluctant to adopt cloud computing adoption (Al-Dwairi et al, 2018) (Rababah and Al-nassar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PaaS, and SaaS adopters are less likely to adopt since switching cost is less and the exit barrier is less difficult than IaaS. Gangwar et al (2015), and [45,58] reported that there is a significant relationship between competitive pressure and the adoption in Indian companies and Malaysian SMEs. On the other hand, Oliveira et al (2014), and Alismaili et al (2016) [23,35] claimed that competitive pressure is not significantly important.…”
Section: -2-implication and Explanation Of Findings And Comparison With Other Studiesmentioning
confidence: 99%
“…On the other hand, Oliveira et al (2014), and Alismaili et al (2016) [23,35] claimed that competitive pressure is not significantly important. Competitive pressure has changed depending on the region [45,58]. Far East countries are also more likely to be affected in Indian and Malaysian companies Gangwar et al (2015) [45,58] respectively.…”
Section: -2-implication and Explanation Of Findings And Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation